Inhibition of para‐Hydroxyphenylpyruvate Dioxygenase by Analogues of the Herbicide Nitisinone As a Strategy to Decrease Homogentisic Acid Levels, the Causative Agent of Alkaptonuria. (7th March 2016) - Laschi, Marcella; Bernardini, Giulia; Dreassi, Elena; Millucci, Lia; Geminiani, Michela; Braconi, Daniela; Marzocchi, Barbara; Botta, Maurizio; Manetti, Fabrizio; Santucci, Annalisa
Abstract: Alkaptonuria (AKU) is a rare multisystem metabolic disease caused by deficient activity of homogentisate 1, 2‐dioxygenase (HGD), which leads to the accumulation of homogentisic acid (HGA). Currently, there is no treatment for AKU. The sole drug with some beneficial effects is the herbicide nitisinone (1 ), an inhibitor of p ‐hydroxyphenylpyruvate dioxygenase (4‐HPPD).1 has been used as a life‐saving drug in infants with type I tyrosinemia despite severe side effects due to the buildup of tyrosine. Four clinical trials of nitisinone to treat AKU have shown that1 consistently decreases HGA levels, but also caused the accumulation of tyrosine in blood serum. Moreover, the human preclinical toxicological data for1 are incomplete. In this work, we performed pharmacodynamics and toxicological evaluations of1, providing the first report of LD50 values in human cells. Intracellular tyrosinemia was also evaluated. Three additional 4‐HPPD inhibitors with a more favorable profile than that of1 in terms of IC50, LD50, and tyrosine accumulation were also identified among commercially available compounds. These may be promising starting points for the development of new therapeutic strategies for the treatment of AKU. Abstract : A better stop 4‐HPPD : Alkaptonuria (AKU) is a rare and serious multisystem debilitating disease with no licensed treatment. Nitisinone is used to treat AKU despite severe hypertyrosinemia and incomplete preclinical human toxicological data. This study provides the first determinations of LD50 values in human cells and suggests the use of alternative compounds as promising scaffolds for developing new therapeutic strategies for treatment of AKU.